2023
DOI: 10.23876/j.krcp.22.026
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post-contrast acute kidney injury in patients sequentially administered iodine- and gadolinium-based contrast media on the same visit to the emergency department: a retrospective study

Abstract: Background: This study compares the incidence of post-contrast acute kidney injury (PC-AKI) in patients who received a single administration of iodine-based contrast medium (ICM) with that in patients who received a sequential administration of ICM and gadolinium-based contrast agents (GBCA) in a single visit to an emergency department (ED) to determine the risk factors for PC-AKI. Methods: Patients who received one or more contrast media in the ED from 2016 to 2021 were included in this retrospective study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although initially believed to be without major adverse effects, gadolinium-based contrast agents was demonstrated to cause nephrogenic systemic fibrosis in patients with abnormal renal function [ 5 ]; moreover, a recent study indicated that exposure to Gadolinium was related to both necrosis and apoptosis of proximal tubular epithelium which led to kidney injury after Gadolinium exposure [ 6 , 7 ]. A retrospective study found that sequential exposure to iodine- and gadolinium-based contrast media on the same admission was a risk factors for post-contrast acute kidney injury (AKI) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially believed to be without major adverse effects, gadolinium-based contrast agents was demonstrated to cause nephrogenic systemic fibrosis in patients with abnormal renal function [ 5 ]; moreover, a recent study indicated that exposure to Gadolinium was related to both necrosis and apoptosis of proximal tubular epithelium which led to kidney injury after Gadolinium exposure [ 6 , 7 ]. A retrospective study found that sequential exposure to iodine- and gadolinium-based contrast media on the same admission was a risk factors for post-contrast acute kidney injury (AKI) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-associated acute kidney injury (CA-AKI) is characterized by a decrease in kidney function that occurs within several days after the intravascular administration of contrast material during imaging examination [ 1 , 2 ], which is similar with post-contrast acute kidney injury [ 1 , 8 ] and includes contrast-induced AKI (CI-AKI) [ 9 ]. The diagnosis of CI-AKI requires a causal temporality between contrast media and AKI as well as excluding other possible causes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation